Inhibition of enterotoxigenic Escherichia Coli (ETEC) adhesion to caco-2 cells by human milk and its immunoglobulin and non-immunoglobulin fractions. - Oliveira, Inaiara Rosa de (2007)
Enterotoxigenic Escherichia coli (ETEC) is the most common cause of diarrhea in children in developing countries and among travelers to ETEC endemic areas. ETEC diarrhea is caused by colonization of the small intestine mediated by colonization factor (CF) antigens, and subsequent elaboration of enterotoxins. Breast feeding has been related to protection against enteric infections. The protective effect of human milk can be ascribed to its immunoglobulin content, specially secretory immunoglobulin A (sIgA), and to nonimmunoglobulin components such as free oligosaccharides, glycoproteins and glycolipids. In this study we investigated the effect of whole human milk and its fractions immunoglobulin and non-immunoglobulin on the adherence of ETEC strains possessing different CFs to Caco-2 cells, as well as the ability of sIgA and free secretory component (fSC) to bind to bacterial superficial proteins. Pooled human milk from three donors were fractionated by gel filtration and analyzed by SDS-PAGE. Our results revealed that whole human milk and its proteins fractions, containing sIgA and fSC, inhibited adhesion ETEC strains harboring different colonization factors antigens. We also verified that sIgA and fSC, using immunoblotting and immunogold labeling assays, bound to some fimbrial proteins and other material present in bacterial surface. Our findings suggest that whole human milk and its fractions may contribute to protection against ETEC infections by blocking bacterial adhesion mediated by different colonization antigens.